Problematika Siswa dalam Implementasi Model Pembelajaran Mind Mapping pada Pembelajaran PAI - Lola Pratika; Indah Muliati (Pendidikan Islam Anak Usia Dini STIT Palapa Nusantara, 2022)
Mind Mapping is a learning model that can make it easier for students to understand and remember subject matter and can map material into students' minds by taking creative and innovative notes based on the material they understand. When carrying out the learning process sometimes there are some problems experienced by students. The formulation of the problem determined in this study is what are the problems felt by students when the teacher implements the mind mapping learning model in PAI learning in class XI SMA Negeri 1 Lembah Gumanti. The purpose of this study is to describe what problems are felt by students when the teacher implements the mind mapping learning model in PAI learning in Class XI SMA Negeri 1 Lembah Gumanti. This research is a qualitative research with descriptive type. The data in this study the authors obtained by using observation techniques, interviews, and documentation. The data was analyzed through three stages, namely data reduction, data presentation, and drawing conclusions. The results of the research that the author conducted showed that when the teacher implemented the mind mapping learning model there were problems felt by the students, both from the cognitive aspect, the affective aspect, and the student's psychomotor aspect. The problems experienced by students in cognitive aspects such as the ability to understand learning materials, the ability to store the acquisition of learning outcomes in the form of material points made into mind mapping and students feel out of ideas in creativity when making mind mapping. The problems experienced by students in the affective aspect are the low interest and motivation of students to learn and easily give up if there are obstacles in the process of making mind mapping, and the last problem experienced by students in the psychomotor aspect is that students do not summarize the material into points but make ideas such as paragraphs. , there is no central image in mind mapping, students make mind mapping with the position of the paper in portrait, students make mind mapping on the top of the paper not in the middle of the paper, and use lined paper in making mind mapping.